Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/bip.21078
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of the MHC class II peptide binding cleft in the bound, partially filled, and empty states: A molecular dynamics simulation study

Abstract: Major histocompatibility (MHC) Class II cell surface proteins present antigenic peptides to the immune system. Class II structures in complex with peptides but not in the absence of peptide are known. Comparative molecular dynamics (MD) simulations of a Class II protein (HLA‐DR3) with and without CLIP (invariant chain‐associated protein) peptide were performed starting from the CLIP‐bound crystal structure. Depending on the protonation of acidic residues in the P6 peptide‐binding pocket the simulations stayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 59 publications
11
57
0
Order By: Relevance
“…For each region, we then measured how the distance of the centers of mass varied during the simulation. In both subtypes, the peptide-bound binding groove showed the lowest width variation, similarly to published data [5,32]. Empty B*27:09 showed an intermediate width variation between that of the empty B*27:05 and peptide-bound complexes, especially in regions II and III, as We next hypothesized that if empty B*27:05 was indeed more conformationally disordered than empty B*27:09, it should expose a larger proportion of its F pocket to the solvent.…”
Section: The Binding Groove Width Of Empty B*27:05 Variessupporting
confidence: 88%
“…For each region, we then measured how the distance of the centers of mass varied during the simulation. In both subtypes, the peptide-bound binding groove showed the lowest width variation, similarly to published data [5,32]. Empty B*27:09 showed an intermediate width variation between that of the empty B*27:05 and peptide-bound complexes, especially in regions II and III, as We next hypothesized that if empty B*27:05 was indeed more conformationally disordered than empty B*27:09, it should expose a larger proportion of its F pocket to the solvent.…”
Section: The Binding Groove Width Of Empty B*27:05 Variessupporting
confidence: 88%
“…Several factors indicate that the conformation observed in the αF54C mutant can be adopted by the WT and is relevant to DMmediated peptide exchange. Modeling studies of MHC II suggest that the N-terminal side of the peptide binding site undergoes conformational alteration concurrent with peptide release (32)(33)(34). In a molecular dynamics simulation of peptide-free MHC II (32), we observed changes strikingly similar to those observed in the αF54C structure determined here, in particular, a change in pitch and partial unwinding of the 3 10 helix and concerted rotamer changes of αF51,αF45, αF48 and βF89 (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 65%
“…6, orange). Computational studies suggest that the conformation of the peptide-free protein has alterations near the P1 pocket as well as elsewhere in the binding groove (32)(33)(34), with the α-subunit extended stand region occupying part of the canonical peptide binding site (32), creating a peptide refractive state. In the model shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…38) In class II MHC, some experimental and computational studies indicated that the introduction of a short peptide composed of two residues or G b86Y substitution to occupy only the "N-terminal side" pocket induced a significant stabilization of not only the pocket but also of the whole peptide-binding groove. 14,18,20) The other computational studies discussed the peptide-free form of class II MHC and demonstrated the flexibility of the "N-terminal side" pocket and its importance in peptide-binding over the other pockets. 16,19) Considering these circumstances, our results suggest that the membrane-proximal domains of class II MHC have a greater influence upon peptide-binding than those of class I MHC.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Moreover, some experimental and theoretical studies of the peptide-free platform domain have received attention because its structure has not yet been crystallized in both classes. [10][11][12][13][14][15][16][17][18][19][20] On the other hand, the two membrane-proximal domains have attracted less interest than the platform domain. Some biochemical studies investigated the two membrane-proximal domains of class I MHC, suggesting the importance of b 2 m in peptide-binding.…”
mentioning
confidence: 99%